Afro-féminisme et écriture critique à Cuba - Sandra Monet-Descombey Hernández (Caravelle)
This article presents a reflection on the essays of some contemporary authors, in critical texts published during the two decades 1990-2000 up to 2010, aiming to put forward the racial theme’s evolution (ethnocultural and historical perspective) from feminist and/or feminine point of view, through identitary and cultural representations, particularly in the precursory publications of Nancy Morejón and in the work of other writers or researchers that bring a new visibility to women known today as Afro-Cubans.